The Influence of Education on Increasing Knowledge of Balanced Nutrition in Students at Sman 19 Pekan baru - Sa'bania, Yaumil; Aulawi, Tahrir; Emilia Diestisien, Yanti (Journal of Nutrition and Public Health, 2026)
Background: Adolescents are the nation's future assets, whose development is greatly influenced by nutritional intake. However, many high school students still lack a grasp of the concept of balanced nutrition, which can lead to problems such as malnutrition, obesity, and digestive disorders. This lack of nutritional knowledge leads adolescents to choose foods based solely on their five senses without considering their nutritional value. Therefore, educational interventions are needed to improve their understanding of healthy eating patterns. Aims: This study aims to determine the effect of providing nutrition education on improving students' knowledge of balanced nutrition at SMAN 19 Pekanbaru. The main focus of this study was to determine whether there was a significant difference in students' knowledge levels before (pre-test) and after (post-test) the intervention, which involved education using specific media. Methods:This study used a pre-experiment design with a one-group pretest-posttest model, conducted in May 2025. The sample consisted of 86 students in grades 10 and 11 selected using a purposive sampling method. Education was provided through leaflets covering the pillars of balanced nutrition, messages about balanced nutrition, the contents of my plate, and the impact of nutritional deficiencies or excesses. Data were analyzed bivariately using a paired t-test because the data were normally distributed. Result: The study results showed a significant increase in respondents' knowledge of balanced nutrition after receiving education. The educational process, which included the distribution of leaflets, a 30-minute explanation of the material, and a question-and-answer session, proved effective in improving student understanding. This was evident in the comparison of pre-test and post-test scores measured using a validated questionnaire. Conclusion:It can be concluded that providing nutrition education through leaflets has a positive effect on improving students' knowledge of balanced nutrition at SMAN 19 Pekanbaru. This medium is effective because it is simple, inexpensive, and portable, allowing students to study the information repeatedly to help them make healthier food choices.